Synergistic Outcomes in Drug Delivery: Exploring Harmonious Architectures of Interpenetrating Polymer Networks - Bali, Samriddhi; Bandral, Shubhdeep Singh; Kumar, Mohit; Saini, Ankush; Swami, Rajan (Current Drug Research Reviews, 2025)
Pharmaceutical excipients play a crucial role in determining the outcome of delivered therapeutic cargo density. By far, polymers have captured the biggest share in the excipients market. This surge in demand motivated researchers to look for newer and novel polymeric platforms. Interpenetrating polymeric networks (IPN) are a class of polymer in the same polymer blend league, where two different polymer chains penetrate; and align with each other without any sustainable covalent bond. The novel agreement between the polymer chains equips the IPN with the characteristic features of each participating polymer unit, thus making IPN superior to its predecessors. IPN has crossed a long path, especially in the pharmaceutical medicine field, from the mere coinage of the term to widespread usage, especially in drug delivery, where they increased the bioavailability and efficacy of the co-delivered drugs. The current review will highlight the major studies that have led to the current face of the IPN in various pharmaceutical domains. The present review was conducted by comprehensively reviewing published reports within the recent period using multiple keywords related to IPN and its role in drug delivery. Moving forward, continued exploration and innovation in IPN technologies promise to further enhance their applications, offering novel solutions for the challenges in drug delivery and therapeutic cargo density.
Keywords: covalent bond